دور العرب والفرس في مكافحة الاستعمار البرتغالي في الخليج (دراسة مقارنة) - العقاد, صلاح (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations -- Oman -- Portugal

Some Notes on the Portuguese in Oman = بعض الملاحظات عن البرتغاليين في عمان - Backingham, C. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations -- Oman -- Portugal

New light on the Relationships of Oman and Portuguese (1613-1633) = ملاحطات جديدة عن الصلات بين العمانيين والبرتغاليين - Boxer, C.R. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations -- Oman -- Portugal

معركة تحرير مسقط - رميض, غانم محمد (الوثيقة, 1988)
The conquest of Muscat from the Portuguese in 1648.
Keywords: Relations -- Oman -- Portugal

الرحالة البرتغاليون في الخليج العربي خلال القرنين السادس عشر والسابع عشر - الحمداني, طارق نافع (الوثيقة, 1989)
Portuguese, Turkish, British and Arab published sources are treated, as well as source-material and foreign and Arab studies. The Omani sources have almost neglected the events of the Portuguese invasion of the Arab Gulf altogether. Possible reasons for this are given by Ghannām 1979 (here pp. 205-204). Ḥamadānī, Ṭāriq Nāfiʿ al-: Dirāsa fī ‘l-Wathā’iq wa’l-Maṣādir al-manshūra ʿan il-Ghazw wa’l-Sayṭara al-Burtughāliyya fī ‘l-Khalīj al-ʿArabī. Al-Wathīqa (Bahrain), 6th year nr. 12 (Jum. I 1408/Jan. 1988), 80-103.
Keywords: Relations -- Oman -- Portugal

Omani-Portuguese history - Maamiry, Ahmed Hamoud (Lancers Publishers, 1982)
Keywords: Relations -- Oman -- Portugal

New light on the relations between the Portuguese and the Omanis, 1613-1633 - Boxer, C.R. (Journal of Oman Studies, 1983)
Keywords: Relations -- Oman -- Portugal

Some notes on the Portuguese in Oman - Beckingham, C.F. (Journal of Oman Studies, 1983)
Keywords: Relations -- Oman -- Portugal

Struggle between the Portuguese and the Arabs of Oman for supremacy in the Persian Gulf and the Indian Ocean - Ali, Abdul (Hamdard Islamicus, 1986)
Keywords: Relations -- Oman -- Portugal